FISH glossary: an overview of the fluorescence in situ hybridization technique - Emanuela V. Volpi; Joanna M. Bridger (BioTechniques, 2008)
The introduction of FISH (fluorescence in situ hybridization) marked the beginning of a new era for the study of chromosome structure and function. As a combined molecular and cytological approach, the major advantage of this visually appealing technique resides in its unique ability to provide an intermediate degree of resolution between DNA analysis and chromosomal investigations while retaining information at the single-cell level. Used to support large-scale mapping and sequencing efforts related to the human genome project, FISH accuracy and versatility were subsequently capitalized on in biological and medical research, providing a wealth of diverse applications and FISH-based diagnostic assays. The diversification of the original FISH protocol into the impressive number of procedures available these days has been promoted throughout the years by a number of interconnected factors: the improvement in sensitivity, specificity and resolution, together with the advances in the fields of fluorescence microscopy and digital imaging, and the growing availability of genomic and bioinformatic resources. By assembling in a glossary format many of the “acronymed” FISH applications published so far, this review intends to celebrate the ability of FISH to re-invent itself and thus remain at the forefront of biomedical research.